The Potential of Energy Refurbishment Through the Integration of Daylight Harvesting for Office Buildings in Universiti Sains Islam Malaysia - Arabi, F; Husini, EM; Ismail, WNW; Ja'afar, NH (Amer Scientific Publishers, 2024)
Indexed by Scopus